Encounter rates and abundance of humpback whales (Megaptera novaeangliae) in Gerlache and Bransfield Straits, Antarctic Peninsula - Secchi, Eduardo R.; Dalla Rosa, Luciano; Kinas, Paul G.; Nicolette, Raquel F.; Rufino, Anne N. M.; Azevedo, Alexandre F. (J. Cetacean Res. Manage., 2020)
During the austral summer of 2006, the Projeto Baleias/Brazilian Antarctic Program (PROANTAR) conducted ship surveys for estimating whale encounter rates and abundance in Gerlache and Bransfield Straits, westward of the Antarctic Peninsula (edge between IWC Areas I and II). The encounter rate was higher in the Bransfield Strait (0.32 groups n. mile–1; 95% CI: 0.26–0.39) than in the Gerlache Strait (0.24 groups n. mile–1; 95% CI: 0.13–0.44), though the difference was not statistically evident. An abundance estimate using conventional distance sampling methods was computed only for the Bransfield Strait. The perpendicular distance data was best fitted by the half-normal model without adjustments. Derived abundance for the surveyed area was 865 humpback whales (95% CI = 656–1,141; CV = 14.13). This area represents only a small fraction of the Stock G feeding ground.